Relația dintre performanță, inteligență emoțională, anxietate și coping în rândul jucătorilor de fotbal (Studia Doctoralia Psychology and Educational Science, 2015)
The major objective of this research was to capture the relationship between work performance, emotional intelligence, anxiety, and coping strategies among football players.Preliminary results show that the emotional intelligence variable is a very good predictor of work performance among football players, explaining 41% of the performance variance. As for the anxiety variable, it did not have significant effects on performance. Also, significant correlations have been identified between emotional intelligence and cautious action, as coping strategy.
Keywords: football players; coping strategies; performance; emotional intelligence